Body temperature and its regulation. Issue 9 (September 2018) - Kuht, James; Farmery, Andrew D
Abstract: Humans are homeotherms, i.e. they fix their temperature regardless of their environment. This is vital for normal cellular function and for metabolism to be independent of external temperature. The body has a warm 'core' and a cooler peripheral 'shell' whose role is to regulate heat transfer in and out of the core. Body temperature is controlled by a feedback system with both peripheral and central sensors, and an integrator located in the hypothalamus. Anaesthesia exposes patients to thermoregulatory challenges due to enhanced heat loss from the core to the shell to the environment, and interference with the hypothalamic temperature 'set-point'. In extreme circumstances, deliberate hypothermia may provide benefits that outweigh the risks.